Safe and Sound? Scientists' Understandings of Public Engagement in Emerging Biotechnologies - Braun, Matthias; Starkbaum, Johannes; Dabrock, Peter (PLoS ONE, 2015)
Science communication is a widely debated issue, particularly in the field of biotechnology. However, the views on the interface between science and society held by scientists who work in the field of emerging biotechnologies are currently insufficiently explored. Therefore filling this gap is one of the urgent desiderata in the further development of a dialogue-oriented model of science-public interaction. Against this background, this article addresses two main questions: (1) How do the persons who work in the field of science perceive the public and its involvement in science? (2) What preferred modes of communication are stressed by those scientists? This research is based on a set of interviews with full professors from the field of biotechnology with a special focus on synthetic biology. The results show that scientists perceive the public as holding a primarily risk-focused view of science. On the one hand, different forms of science communication are thereby either seen as a chance to improve the public acceptance of science in general and one field of research in particular. On the other hand, the exchange with the public is seen as a duty because the whole of society is affected by scientific innovation. Yet, some of the stakeholders' views discussed here conflict with debates on public engagement in technological innovation.